Polyester resin and method for producing blow molded polyester resin product

JP7639691B2Active Publication Date: 2025-03-05TOYOBO CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021555347
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-26
Filing Date
2021-03-08
Publication Date
2025-03-05
Estimated Expiration
2041-03-08

AI Technical Summary

Benefits of technology

【0019】 本発明の製造方法では、アンチモン、ゲルマニウムおよびチタン以外の金属成分が主たる金属成分であるアルミニウム化合物とリン化合物とからなる重合触媒を用いてポリエステル樹脂を得ており、該重合触媒を用いて得られたポリエステル樹脂の特徴である色調や耐熱性等の各種安定性を有するうえに、アルミニウム系異物の生成が抑制されており透明性が高い。また、本発明の製造方法では、ポリエステルのヒドロキシル基末端の一部が、リン化合物により封鎖されて、ポリエステル樹脂の製造工程およびポリエステル樹脂をブロー成形する成形工程におけるCTおよびΔCTの生成が抑制されるので、成形用の金型汚染が抑制できるという効果が発現される。さらに、想定外の効果として、アルミニウム化合物とリン化合物からなるポリエステル重合触媒を用いたときには、アンチモン触媒を用いたときに比べて固相重合活性が劣るという課題も改善できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639691000013
    Figure 0007639691000013
  • Figure 0007639691000014
    Figure 0007639691000014
  • Figure 0007639691000015
    Figure 0007639691000015
Patent Text Reader

Abstract

The present invention achieves both decrease of cyclic trimers contained in a polyester resin and decrease of cyclic trimers produced during molding of a blow molded body in cases where a polymerization catalyst that is formed of an aluminum compound and a phosphorus compound is used. A method for producing a polyester resin that contains 85% by mole or more of an ethylene terephthalate structural unit, said method comprising: a melt polymerization step wherein melt polymerization is continuously performed by means of two or more polymerization vessels, while using an aluminum compound and a phosphorus compound as a polymerization catalyst, in such a manner that polymerization in the last polymerization vessel satisfies the condition of formula (I) described below; and a solid-phase polymerization step wherein solid-phase polymerization is performed after the melt polymerization step. (I): 410 ≤ T × RT × (P / Al) ≤ 580 (In formula (I), T represents the temperature (°C) of the last polymerization vessel; RT represents the residence time (hour) of the last polymerization vessel; and P / Al represents the molar ratio of elemental phosphorus to elemental aluminum in the polyester resin.)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polyester resin and a blow molded article made of a polyester resin. [Background technology]

[0002] Polyester resins, such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), etc., have excellent mechanical and chemical properties, and are used in a wide range of fields, such as fibers for clothing and industrial materials, films and sheets for packaging, magnetic tapes, and optics, hollow molded bottles, casings for electric and electronic components, and other engineering plastic molded products, depending on the properties of each polyester resin. In particular, bottles made of saturated polyester resins such as PET are excellent in mechanical strength, heat resistance, transparency, and gas barrier properties, and are therefore widely used as containers for filling beverages such as juices, carbonated drinks, and soft drinks, as well as containers for eye drops, cosmetics, etc.

[0003] A typical polyester resin, whose main components are units derived from aromatic dicarboxylic acids and alkylene glycols, is produced, for example in the case of PET, by producing an oligomer mixture such as bis(2-hydroxyethyl) terephthalate through an esterification reaction or transesterification reaction between terephthalic acid or dimethyl terephthalate and ethylene glycol, and then melt-polymerizing this at high temperature in a vacuum using a catalyst.

[0004] Conventionally, antimony compounds or germanium compounds have been widely used as polyester polymerization catalysts used in the polymerization of such polyester resins. Antimony trioxide, an example of an antimony compound, is a catalyst that is inexpensive and has excellent catalytic activity, but when it is used as the main component, that is, in an amount that provides a practical polymerization rate, metallic antimony precipitates during polymerization, causing blackening and foreign matter in the polyester resin, which also causes surface defects in the film. In addition, when it is used as a raw material for hollow molded products, it is difficult to obtain hollow molded products with excellent transparency. For these reasons, there is a demand for polyester resins that do not contain antimony at all or do not contain antimony as the main catalyst component.

[0005] As a catalyst that has excellent catalytic activity other than antimony compounds and gives polyester resins that do not have the above problems, germanium compounds have already been put to practical use. However, germanium compounds have problems in that they are very expensive, and they are prone to distill out of the reaction system during polymerization, which changes the catalyst concentration in the reaction system and makes it difficult to control the polymerization, making it problematic to use them as the main catalyst component.

[0006] Studies are also being conducted on polymerization catalysts that can replace antimony compounds or germanium compounds, and titanium compounds, such as tetraalkoxy titanates, have already been proposed. However, polyester resins produced using titanium compounds are susceptible to thermal degradation during melt molding, and have the problem of being significantly colored.

[0007] In view of the above, there is a demand for a polymerization catalyst which contains a metal component other than antimony, germanium, and titanium as the main metal component of the catalyst, and which gives polyester resins which have excellent catalytic activity, excellent color tone and thermal stability, and excellent transparency in molded products.

[0008] One of the applications of polyester resin is blow molded articles. In blow molded articles made of polyester resin, high transparency of the molded article is desired, and a catalyst composed of an aluminum compound and a phosphorus compound has been disclosed as a new polymerization catalyst (for example, see Patent Document 1).

[0009] Furthermore, when a catalyst consisting of an aluminum compound and a phosphorus compound is used, it is necessary to suppress the generation of aluminum-based foreign matter in order to obtain a polyester resin with high transparency. Patent Document 2 discloses a method for suppressing the generation of aluminum-based foreign matter.

[0010] However, when the method of Patent Document 1 is carried out, there is a problem that the transparency of the obtained polyester resin varies depending on the amounts and composition ratios of the aluminum compound and phosphorus compound added, which are the catalyst composition.

[0011] On the other hand, by implementing the method of Patent Document 2, it is possible to suppress the generation of aluminum-based foreign matter, which is the problem described above, and to obtain a polyester resin and a polyester resin blow molded article with high transparency. However, there is a problem with polyester resin blow molded articles in that the cyclic trimer (hereinafter referred to as CT) contained in the polyester resin and the cyclic trimer (hereinafter referred to as ΔCT) generated during molding cause dirt to adhere to the mold used during molding, and this mold dirt causes problems such as a deterioration in transparency during continuous molding. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] JP 2004-256633 A [Patent Document 2] Patent No. 5299655 Summary of the Invention [Problem to be solved by the invention]

[0013] The present invention has been made against the background of the problems of the conventional technology described above, and has an object to provide a polyester resin obtained using a polymerization catalyst composed of an aluminum compound and a phosphorus compound, the main metal component of which is a metal component other than antimony, germanium, and titanium, which has various stabilities such as color tone and heat resistance, which are characteristic of the polyester resin obtained using the polymerization catalyst, while suppressing the generation of aluminum-based foreign matter and providing high transparency, and further suppressing mold contamination during the production of polyester resin blow molded articles by achieving both a reduction in the CT amount and a reduction in the ΔCT amount, and improving the problem of a low solid-phase polymerization rate, which is one of the problems in the method for producing a polyester resin using a polymerization catalyst composed of an aluminum compound and a phosphorus compound. [Means for solving the problem]

[0014] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems, and as a result discovered a method for suppressing mold contamination due to CT and ΔCT during the production of polyester resin blow molded articles, which had not been solved by conventional techniques, and for improving the quality and productivity of polyester resin blow molded articles, thereby arriving at the present invention.

[0015] The CT amount and ΔCT amount behave in a trade-off manner, as described below. Therefore, the present inventors aimed to establish a method for reducing both CT and ΔCT, suppressing the total amount of CT and ΔCT, and suppressing mold fouling. Patent Document 2 is a method established by focusing on a specific structure of phosphorus compounds present in polyester resins. Meanwhile, it has been found that there are nine types of phosphorus compounds present in polyester resins, including the structure focused on in Patent Document 2. The phosphorus compounds include phosphorus compounds bonded to the hydroxyl group terminals of polyesters, which are represented by (Chemical Formula 1) to (Chemical Formula 3) described below. On the other hand, CT and ΔCT in polyester resins are presumed to be produced by the cyclization depolymerization of the hydroxyl end of the polyester, that is, the backbiting reaction, in which the hydroxyl end of the polyester attacks the third ester bond from the end, as shown in the chemical formula below.

[0016] [ka]

[0017] The present inventors conducted various studies under the above circumstances, believing that by increasing the amount of the compounds of the above-mentioned (Formula 1) to (Formula 3) and thereby decreasing the hydroxyl group concentration in the polyester resin, the back-biting reaction of the hydroxyl group terminals can be suppressed and the formation of CT and ΔCT can be suppressed, and the present invention was completed. Furthermore, as an unexpected effect of the above studies, it was also found that when a polyester polymerization catalyst consisting of an aluminum compound and a phosphorus compound is used, the problem of poor solid-phase polymerization activity can be improved compared to when an antimony catalyst is used.

[0018] The present invention has been completed based on the above findings, and has the following features (1) to (10). (1) A method for producing a polyester resin containing 85 mol % or more of ethylene terephthalate structural units, comprising the steps of: a melt polymerization step in which an aluminum compound and a phosphorus compound are used as polymerization catalysts to continuously melt-polymerize in two or more polymerization tanks, and the polymerization in the final polymerization tank satisfies the condition of the following formula (I); A method for producing a polyester resin, comprising the steps of: performing solid-phase polymerization after the melt polymerization step; 410≦T×RT×(P / Al)≦580… (I) [In the above formula (I), T represents the temperature (° C.) of the final polymerization tank, RT represents the residence time (hours) in the final polymerization tank, and P / Al represents the molar ratio of phosphorus element to aluminum element in the polyester resin.] (2) The method for producing a polyester resin according to the above (1), wherein the phosphorus compound is heat-treated in a solvent at 150 to 200°C. (3) The method for producing a polyester resin according to the above (1) or (2), wherein the phosphorus compound is at least one selected from the group consisting of phosphonic acid compounds and phosphinic acid compounds. (4) The method for producing a polyester resin according to any one of (1) to (3) above, wherein the total amount of phosphorus elements bonded to hydroxyl terminals of the polyester is 42 to 60 mol % relative to the total amount of phosphorus elements present in the polyester resin. (5) The method for producing a polyester resin according to any one of the above (1) to (4), wherein the polyester resin has a cyclic trimer content of 3,300 ppm or less. (6) The method for producing a polyester resin according to any one of (1) to (5) above, wherein the moisture content of the polyester resin is 100 ppm or less, and the amount of cyclic trimer generated when the polyester resin is melt-molded at a cylinder temperature of 290°C in an injection molding machine is 650 ppm or less. (7) The method for producing a polyester resin according to any one of (1) to (6) above, wherein the structure of a phosphorus compound bonded to a hydroxyl group terminal of the polyester resin is at least one of the structures represented by the following (Chemical Formula 1) to (Chemical Formula 3). [ka] [ka] [ka] (8) The method for producing a polyester resin according to any one of the above (1) to (7), wherein the content of aluminum element in the polyester resin is 13 to 25 ppm. (9) The method for producing a polyester resin according to any one of the above (1) to (8), wherein the molar ratio of phosphorus element to aluminum element (P / Al) in the polyester resin is 1.5 to 3.5. (10) A method for producing a blow-molded polyester resin product, comprising the step of blow-molding a polyester resin produced by the method for producing a polyester resin according to any one of (1) to (9) above. Effect of the Invention

[0019] In the manufacturing method of the present invention, a polyester resin is obtained using a polymerization catalyst consisting of an aluminum compound and a phosphorus compound, the main metal components of which are metal components other than antimony, germanium, and titanium. The polyester resin obtained using the polymerization catalyst has various stabilities such as color tone and heat resistance, which are characteristic of the polyester resin, and is highly transparent because the generation of aluminum-based foreign matter is suppressed. In addition, in the manufacturing method of the present invention, a part of the hydroxyl group terminal of the polyester is blocked by a phosphorus compound, and the generation of CT and ΔCT in the manufacturing process of the polyester resin and the molding process of blow molding the polyester resin is suppressed, so that the effect of suppressing mold contamination for molding is achieved. Furthermore, as an unexpected effect, when a polyester polymerization catalyst consisting of an aluminum compound and a phosphorus compound is used, the problem of poor solid-phase polymerization activity compared to when an antimony catalyst is used can also be improved. [Brief description of the drawings]

[0020] [Figure 1] FIG. 2 is a correlation diagram between T×RT×(P / Al) and CT and ΔCT in the final polymerization vessel, determined from the results of Examples and Comparative Examples. [Diagram 2] FIG. 2 is a correlation diagram between T×RT×(P / Al) in the final polymerization tank and the total CT amount (=CT amount+ΔCT amount) obtained from the results of Examples and Comparative Examples. [Diagram 3] FIG. 2 is a correlation diagram between T×RT×(P / Al) in the final polymerization vessel and the amount of end-capped phosphorus compound, determined from the results of Examples and Comparative Examples. [Figure 4] FIG. 2 is a correlation diagram between the amount of end-capped phosphorus compound and the total CT amount (=CT amount+ΔCT amount) obtained from the results of Examples and Comparative Examples. [Diagram 5] FIG. 2 is a correlation diagram between the amount of a terminal-blocked phosphorus compound and the solid-phase polymerization rate, determined from the results of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will be described in detail below.

[0022] (polyester resin) The polyester resin obtained by the production method of the present invention contains 85 mol % or more, more preferably 90 mol % or more, and even more preferably 95 mol % or more of ethylene terephthalate structural units. The polyester resin obtained by the production method of the present invention preferably comprises a polyvalent carboxylic acid and / or an ester-forming derivative thereof and a polyhydric alcohol and / or an ester-forming derivative thereof.

[0023] The polycarboxylic acid is preferably a dicarboxylic acid, and particularly preferably terephthalic acid, but may contain a dicarboxylic acid other than terephthalic acid. Examples of dicarboxylic acids other than terephthalic acid include saturated aliphatic dicarboxylic acids or ester-forming derivatives thereof, such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedicarboxylic acid, dodecanedicarboxylic acid, tetradecanedicarboxylic acid, hexadecanedicarboxylic acid, 1,3-cyclobutanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,5-norbornanedicarboxylic acid, and dimer acid; and unsaturated aliphatic dicarboxylic acids, such as fumaric acid, maleic acid, and itaconic acid. and aromatic dicarboxylic acids such as phthalic acid or ester-forming derivatives thereof, orthophthalic acid, isophthalic acid, terephthalic acid, 5-(alkali metal)sulfoisophthalic acid, diphenic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, 4,4'-biphenylsulfonedicarboxylic acid, 4,4'-biphenyletherdicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, pamoic acid, and anthracenedicarboxylic acid, or ester-forming derivatives thereof.

[0024] In addition to dicarboxylic acids, a small amount of a polyvalent carboxylic acid having three or more valences may be used in combination, and a polyvalent carboxylic acid having three or four valences is preferable. Examples of the polyvalent carboxylic acid include ethanetricarboxylic acid, propanetricarboxylic acid, butanetetracarboxylic acid, pyromellitic acid, trimellitic acid, trimesic acid, 3,4,3',4'-biphenyltetracarboxylic acid, and ester-forming derivatives thereof.

[0025] The polyhydric alcohol is preferably a diol, particularly preferably ethylene glycol, but may contain a diol other than ethylene glycol. Examples of diols other than ethylene glycol include 1,2-propylene glycol, 1,3-propylene glycol, diethylene glycol, triethylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 1,4-cyclohexanediethanol, 1,10-decamethylene glycol, 1,12- aliphatic glycols exemplified by dodecanediol, polyethylene glycol, polytrimethylene glycol, polytetramethylene glycol, and the like; aromatic glycols exemplified by hydroquinone, 4,4'-dihydroxybisphenol, 1,4-bis(β-hydroxyethoxy)benzene, 1,4-bis(β-hydroxyethoxyphenyl)sulfone, bis(p-hydroxyphenyl)ether, bis(p-hydroxyphenyl)sulfone, bis(p-hydroxyphenyl)methane, 1,2-bis(p-hydroxyphenyl)ethane, bisphenol A, bisphenol C, 2,5-naphthalenediol, glycols obtained by adding ethylene oxide to these glycols, and the like.

[0026] In addition to the diol, a small amount of a polyhydric alcohol having a valence of 3 or more or a hydroxycarboxylic acid may be used in combination, and a polyhydric alcohol having a valence of 3 to 4 is preferable. Examples of the polyhydric alcohol include trimethylolmethane, trimethylolethane, trimethylolpropane, pentaerythritol, glycerol, and hexanetriol. Examples of the hydroxycarboxylic acid include lactic acid, citric acid, malic acid, tartaric acid, hydroxyacetic acid, 3-hydroxybutyric acid, p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, 4-hydroxycyclohexanecarboxylic acid, and ester-forming derivatives thereof.

[0027] The use of a cyclic ester in combination is also permitted. Examples of the cyclic ester include ε-caprolactone, β-propiolactone, β-methyl-β-propiolactone, δ-valerolactone, glycolide, and lactide.

[0028] Examples of the ester-forming derivatives of polycarboxylic acids or hydroxycarboxylic acids include alkyl esters and hydroxyl alkyl esters of these compounds.

[0029] Examples of the ester-forming derivatives of polyhydric alcohols include esters of polyhydric alcohols with lower aliphatic carboxylic acids such as acetic acid.

[0030] (Polymerization catalyst) The polyester resin obtained by the production method of the present invention is produced using a polymerization catalyst consisting of an aluminum compound and a phosphorus compound, and the aluminum compound and the phosphorus compound may be added in catalytic amounts. The catalytic amount means an effective amount for promoting the reaction between a polyvalent carboxylic acid and / or its ester-forming derivative and a polyhydric alcohol and / or its ester-forming derivative, and specifically, the catalytic amount may be such that a predetermined amount of aluminum element and phosphorus element remains in the obtained polyester resin, as described below.

[0031] (Aluminum Compounds) The aluminum compound constituting the polymerization catalyst is not limited as long as it is soluble in a solvent, and examples of the aluminum compound include carboxylates such as aluminum formate, aluminum acetate, basic aluminum acetate, aluminum propionate, aluminum oxalate, aluminum acrylate, aluminum laurate, aluminum stearate, aluminum benzoate, aluminum trichloroacetate, aluminum lactate, aluminum citrate, aluminum tartrate, and aluminum salicylate; inorganic acid salts such as aluminum chloride, aluminum hydroxide, aluminum hydroxide chloride, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum phosphate, and aluminum phosphonate; aluminum methoxide, aluminum ethoxide, aluminum n-propionate, and the like. Examples of the aluminum alkoxide include aluminum alkoxides such as aluminum isopropoxide, aluminum n-butoxide, and aluminum t-butoxide; chelate compounds such as aluminum acetylacetonate, aluminum ethylacetoacetate, and aluminum ethylacetoacetate diisopropoxide; organic aluminum compounds such as trimethylaluminum and triethylaluminum and partial hydrolysates thereof, reaction products of aluminum alkoxides or aluminum chelate compounds with hydroxycarboxylic acids, aluminum oxide, ultrafine aluminum oxide, aluminum silicate, and composite oxides of aluminum with titanium, silicon, zirconium, alkali metals, and alkaline earth metals. Among these, at least one selected from carboxylates, inorganic acid salts, and chelate compounds is preferred, and among these, at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, aluminum hydroxide chloride, and aluminum acetylacetonate is more preferred, at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, and aluminum hydroxide chloride is even more preferred, and at least one selected from aluminum acetate and basic aluminum acetate is most preferred.

[0032] The aluminum compound is preferably an aluminum compound that is solubilized in a solvent such as water or glycol. The solvent that can be used in the present invention is water and alkylene glycols. Examples of alkylene glycols include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, trimethylene glycol, ditrimethylene glycol, tetramethylene glycol, ditetramethylene glycol, and neopentyl glycol. At least one selected from ethylene glycol, trimethylene glycol, and tetramethylene glycol is preferable, and ethylene glycol is more preferable. It is preferable to use a solution in which an aluminum compound is dissolved in water or ethylene glycol, since the effect of the present invention can be significantly exhibited. From the viewpoint of solubilization, the aluminum compound is preferably at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide chloride, and aluminum acetylacetonate, more preferably at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, and aluminum hydroxide chloride, and most preferably at least one selected from aluminum acetate and basic aluminum acetate.

[0033] The amount of the aluminum compound used is preferably such that the aluminum element is 13 to 25 ppm relative to the total mass of the resulting polyester resin, and more preferably 14 to 20 ppm. If the aluminum element is less than 13 ppm, the polymerization activity may decrease, while if it exceeds 25 ppm, the amount of aluminum-based foreign matter may increase.

[0034] (Phosphorus compounds) The phosphorus compound constituting the polymerization catalyst of the present invention is not particularly limited, but it is preferable to use a phosphonic acid compound or a phosphinic acid compound because it has a large effect of improving the catalytic activity. Among these, it is more preferable to use a phosphonic acid compound because it has a particularly large effect of improving the catalytic activity.

[0035] Among the above phosphorus compounds, phosphorus compounds having a phenol structure in the same molecule are preferred. There are no particular limitations on the phosphorus compounds having a phenol structure, but using one or more compounds selected from the group consisting of phosphonic acid compounds having a phenol structure in the same molecule and phosphinic acid compounds having a phenol structure in the same molecule is preferred because it has a large effect of improving catalytic activity, and using one or more phosphonic acid compounds having a phenol structure in the same molecule is more preferred because it has a very large effect of improving catalytic activity.

[0036] In addition, the phosphorus compound having a phenol structure in the same molecule is P(=O)R 1 (OR 2 )(OR 3 ) or P(=O)R 1 R 4 (OR 2 ) and compounds represented by R 1 R represents a hydrocarbon group having 1 to 50 carbon atoms containing a phenol moiety, a substituent such as a hydroxyl group, a halogen group, an alkoxyl group, or an amino group, and a hydrocarbon group having 1 to 50 carbon atoms containing a phenol structure. 4 R represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms containing a substituent such as a hydroxyl group, a halogen group, an alkoxyl group, or an amino group. 2 , R 3 R each independently represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms containing a substituent such as a hydroxyl group or an alkoxyl group. However, the hydrocarbon group may contain a branched structure, an alicyclic structure such as cyclohexyl, or an aromatic ring structure such as phenyl or naphthyl. 2 and R 4 The ends of may be bonded together.

[0037] Examples of phosphorus compounds having a phenol structure in the same molecule include p-hydroxyphenylphosphonic acid, dimethyl p-hydroxyphenylphosphonate, diethyl p-hydroxyphenylphosphonate, diphenyl p-hydroxyphenylphosphonate, bis(p-hydroxyphenyl)phosphinic acid, methyl bis(p-hydroxyphenyl)phosphinate, phenyl bis(p-hydroxyphenyl)phosphinate, p-hydroxyphenylphenylphosphinic acid, methyl p-hydroxyphenylphenylphosphinate, phenyl p-hydroxyphenylphosphinate, p-hydroxyphenylphosphinic acid, methyl p-hydroxyphenylphosphinate, phenyl p-hydroxyphenylphosphinate, and 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl represented by the following (chemical formula 4). As the phosphorus compound having a phenol structure in the same molecule, a phosphorus compound having a hindered phenol structure is particularly preferred, and among these, 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl represented by the following (chemical formula 4) is preferred.

[0038] [ka] (In formula 4, X 1 , X 2 respectively represent hydrogen and an alkyl group having 1 to 4 carbon atoms.)

[0039] Above X 1 , X 2 The number of carbon atoms in the alkyl group is preferably 1 to 4, and more preferably 1 to 2. In particular, an ethyl ester having 2 carbon atoms is preferred because Irganox 1222 (manufactured by BASF) is commercially available and easily available.

[0040] The amount of phosphorus compound used is preferably such that the phosphorus element is 25 to 60 ppm relative to the total mass of the polyester resin obtained. More preferably, it is 30 to 50 ppm. If the phosphorus element is less than 25 ppm, the polymerization activity may decrease and the amount of aluminum-based foreign matter may increase. On the other hand, if it exceeds 60 ppm, it becomes difficult to simultaneously reduce the CT amount and the ΔCT amount, and the amount of phosphorus compound added increases, which may increase the catalyst cost.

[0041] In the present invention, the phosphorus compound is preferably heat-treated in a solvent. The solvent to be used is not limited as long as it is at least one selected from the group consisting of water and alkylene glycol, but as the alkylene glycol, it is preferable to use a solvent that dissolves the phosphorus compound, and it is more preferable to use a glycol that is a component of the target polyester resin, such as ethylene glycol. The heat treatment in the solvent is preferably performed after dissolving the phosphorus compound, but it is not necessary that the phosphorus compound is completely dissolved.

[0042] The temperature for the heat treatment is not particularly limited, but is preferably 20 to 250°C, and more preferably 150 to 200°C.

[0043] The concentration of the phosphorus compound solution during the heat treatment is preferably 3 to 15% by mass, and more preferably 5 to 15% by mass.

[0044] The above heat treatment improves the activity of the polymerization catalyst when used in combination with the aluminum compound, and also reduces the amount of foreign matter produced by the polymerization catalyst.

[0045] In the above heat treatment, a part of the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester, which is the phosphorus compound shown in (chemical formula 4) used in the present invention, undergoes a structural change. For example, the structure changes to a tert-butyl group elimination, an ethyl ester group hydrolysis, and a hydroxyethyl ester exchange structure. Therefore, in the present invention, the phosphorus compound includes not only the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester shown in (chemical formula 4), but also phosphorus compounds whose structures have been changed as shown in Table 1. The component amount of each phosphorus compound shown in Table 1 in the ethylene glycol solution can be quantified by P-NMR spectroscopy of the solution.

[0046] [Table 1]

[0047] Therefore, the phosphorus compound in the present invention includes not only diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate but also modified products of diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate shown in Table 1 above.

[0048] (Phosphorus compound structure in polyester resin) In polyester resins produced using diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate and its modified products as the phosphorus compound, nine types of structures including the three types of (Chemical Formula 1) to (Chemical Formula 3) described above are present. The nine types of phosphorus compound structures are shown in Table 2. The nine types of phosphorus compound structures shown in Table 2 are also contained in polyester resin blow molded products described later, similar to the polyester resins.

[0049] [Table 2]

[0050] The technology disclosed in the above-mentioned Patent Document 2 is a technology that was established by focusing on (Chemical Formula 5) and (Chemical Formula 6) in Table 2 above.

[0051] As described above, the present invention is based on the idea that the production of CT and ΔCT can be suppressed by increasing the total amount of phosphorus compounds bonded to the hydroxyl group terminals of the polyesters shown in (Chemical Formula 1) to (Chemical Formula 3).

[0052] Therefore, in the present invention, it is preferable that 42 to 60 mol% of the total phosphorus element present in the polyester resin is present by bonding to the hydroxyl group terminal of the polyester, that is, the total amount of phosphorus element contained in (Chemical Formula 1) to (Chemical Formula 3) is 42 to 60 mol% relative to the total amount of phosphorus element present in the polyester resin. The lower limit is more preferably 44 mol% or more, and the upper limit may be 100 mol% since the higher the better, but from the viewpoint of technical difficulties, the upper limit is preferably 60 mol%, more preferably 55 mol%, and even more preferably 50 mol%. The phosphorus compound present by bonding to the hydroxyl group terminal of the polyester is sometimes called a terminal-blocked phosphorus compound.

[0053] By satisfying the above range, it is possible to achieve both a reduction in the CT amount and a reduction in the ΔCT amount. Furthermore, as an unexpected effect, it is possible to improve the problem of polyester polymerization catalysts consisting of aluminum compounds and phosphorus compounds, that is, their solid-state polymerization activity is inferior to that of antimony catalysts. Although the reason why the solid-state polymerization activity is improved by increasing the amount of the end-blocked phosphorus compound of polyester is not clear, it is speculated that this is because the reaction activity between the hydroxyl group terminal and the end-blocked phosphorus compound in the solid-state polymerization reaction is higher than the reaction activity between the carboxyl group terminal and the end-blocked phosphorus compound.

[0054] (Aluminum / phosphorus ratio in polyester resin) In the polyester resin obtained by the production method of the present invention, the molar ratio of phosphorus element to aluminum element (hereinafter referred to as P / Al ratio) is preferably 1.5 to 3.5. The lower limit is more preferably 1.6 or more, and the upper limit is more preferably 3.0 or less, and further preferably 2.4 or less. When the P / Al ratio is less than 1.5, it becomes difficult to simultaneously achieve a reduction in the CT amount and a reduction in the ΔCT amount, and there is a risk of an increase in the amount of aluminum-based foreign matter. On the other hand, when the P / Al ratio exceeds 3.5, it becomes difficult to simultaneously achieve a reduction in the CT amount and a reduction in the ΔCT amount, and there is a risk of an increase in the amount of phosphorus compound added, which increases the catalyst cost. In addition, the polymerization activity also decreases.

[0055] (CT amount in polyester resin) The CT amount contained in the polyester resin obtained by the production method of the present invention is preferably 3300 ppm or less. More preferably, it is 3200 ppm or less, and even more preferably, it is 3100 ppm or less. The lower limit is not limited, but is about 2500 ppm due to technical difficulties. If the CT amount exceeds 3300 ppm, it is not preferable because there is a risk of increased mold contamination during molding.

[0056] (ΔCT amount during melt molding of polyester resin) The moisture content of the polyester resin obtained by the production method of the present invention is preferably 100 ppm or less, and the ΔCT amount when melt-molded at a cylinder temperature of 290°C in an injection molding machine is preferably 650 ppm or less. More preferably, it is 500 ppm or less, and even more preferably, it is 400 ppm or less. The lower limit is preferably 0 ppm, but is about 200 ppm due to technical difficulties. If the ΔCT amount exceeds 650 ppm, it is not preferable because there is a risk of increased mold contamination during molding.

[0057] (Polyester resin blow molding) It is important that the blow molded article of the present invention is a polyester resin blow molded article molded using the above polyester resin. By using the above polyester resin, both the CT amount and the ΔCT amount can be reduced, thereby suppressing contamination of the mold during molding.

[0058] The method for producing the polyester resin blow molded article of the present invention is not limited, and may be, for example, a method including the steps of molding a preform, crystallizing a stopper portion, reheating the preform, blow-stretching the reheated preform in a mold, and heat-setting the blow-stretched hollow molded article in a heated mold.

[0059] Hollow containers made by blow molding polyester resins such as PET are used as containers for a variety of purposes, especially as containers (bottles) for beverages such as juice, tea, and mineral water.

[0060] These beverage containers are broadly classified into pressure-resistant bottles for carbonated beverages, aseptic bottles for aseptic filling, and heat-resistant bottles for high-temperature filling.

[0061] Heat-resistant bottles are filled with the contents at high temperatures of around 80°C, so the bottle must also be heat-resistant so that it does not deform at this filling temperature. Heat resistance is achieved by crystallizing the mouth and body of the bottle.

[0062] Crystallization of the body of the bottle is enhanced by heating the preform, blowing and stretching it in a mold heated to 130-180°C, and then holding the bottle in the mold for an additional 0.5 to 10 seconds.

[0063] At this time, oligomers such as CT in the polyester resin and ΔCT generated during blow molding migrate to the mold surface and contaminate it. With repeated molding, the contamination accumulates, and after a certain number of moldings, the resulting bottle becomes cloudy and loses its commercial value, making it necessary to clean the mold.

[0064] Molds must be cleaned by hand using a solvent and wiping them down. Since a large-scale commercial blow molding machine is equipped with multiple blow molding molds, it takes several hours to a day to finish cleaning all of the molds, which reduces productivity and increases the working environment, and improvements were required.

[0065] Therefore, in the present invention, the content of cyclic trimers in the blow molded article is preferably 3600 ppm or less, more preferably 3500 ppm or less. Although it is preferable that the content of cyclic trimers in the blow molded article is small, from the viewpoint of technical difficulties, it is, for example, 1000 ppm or more, preferably 2000 ppm or more, and more preferably 2700 ppm or more.

[0066] In the present invention, in order to improve the crystallization characteristics of the polyester resin, a resin other than polyethylene terephthalate may be contained. The resin other than polyethylene terephthalate is preferably at least one resin selected from the group consisting of polyolefin resin, polyamide resin, polyacetal resin, and polybutylene terephthalate resin. The blending amount of the resin other than polyethylene terephthalate is preferably 0.1 ppb to 1000 ppm (mass basis), more preferably 0.3 ppb to 100 ppm (mass basis), further preferably 0.5 ppb to 1 ppm (mass basis), and particularly preferably 0.5 ppb to 45 ppb (mass basis).

[0067] The method of blending the above resin with the polyester resin is preferably a method capable of uniformly mixing, such as addition during the polyester resin production process or dry blending with the polyester resin after production, and is preferably added during the polyester resin production process, specifically, at any stage of the esterification reaction or transesterification reaction, or at the beginning of the polymerization reaction process. Also, a method of contacting polyester resin chips with the crystalline resin component is a preferred embodiment.

[0068] (Method to achieve both reduction in CT amount and reduction in ΔCT amount) In the present invention, in order to achieve both a reduction in the CT amount and a reduction in ΔCT, it is preferable that the amount of end-blocked phosphorus compounds in the phosphorus compounds present in the polyester resin is large. Therefore, the method for producing the polyester resin of the present invention includes a melt polymerization step in which an aluminum compound and a phosphorus compound are used as polymerization catalysts, and continuous melt polymerization is performed in two or more polymerization tanks (polymerization tanks performing polycondensation after the esterification reaction / ester exchange reaction steps), and the polymerization in the final polymerization tank satisfies the condition of the following formula (I), and a solid-phase polymerization step in which solid-phase polymerization is performed after the melt polymerization step. In this specification, the "polymerization tank" refers to a polymerization tank performing polycondensation after the esterification reaction / ester exchange reaction steps. 410≦T×RT×(P / Al)≦580… (I) [In the above formula (I), T represents the temperature (° C.) of the final polymerization tank, RT represents the residence time (hours) in the final polymerization tank, and P / Al represents the molar ratio of phosphorus element to aluminum element in the polyester resin.] The end-blocked phosphorus compound is governed by the product of the temperature and residence time of the final polymerization tank in the melt polymerization step of the polyester resin and the product of the molar ratio of phosphorus element and aluminum element remaining in the polyester resin. Therefore, in the present invention, the product of the temperature and residence time of the final polymerization tank is important in the melt polymerization step. The number of the polymerization tanks is more preferably 2 to 5, even more preferably 3 to 4, and most preferably 3.

[0069] The value of the above formula (I) is more preferably 420 or more, even more preferably 450 or more, and particularly preferably 500 or more. The value of the above formula (I) is more preferably 560 or less, and even more preferably 530 or less. If the value of the above formula (1) exceeds 580 or is less than 410, the amount of the end-capped phosphorus compound decreases, thereby increasing the total amount of the CT amount and the ΔCT amount, and there is a risk of increased mold contamination when molding the polyester resin.

[0070] The method for producing the polyester resin of the present invention is not particularly limited, and for example, an oligomer of terephthalic acid or the like and a polyhydric alcohol is obtained by a direct esterification method of a polyvalent carboxylic acid including terephthalic acid and a polyhydric alcohol, or an ester exchange method of an alkyl ester of terephthalic acid or the like and a polyhydric alcohol, and then the oligomer is melt-polymerized under normal pressure or reduced pressure to obtain a polyester resin. In this case, an esterification catalyst or the above-mentioned polymerization catalyst can be used as necessary.

[0071] (Polyester resin melt polymerization process) In the method for producing the polyester resin of the present invention obtained by using a polymerization catalyst consisting of an aluminum compound and a phosphorus compound, the composition of the polyester oligomer fed to the polymerization tank is more affected than that of antimony, germanium, and titanium catalysts. Therefore, it is preferable to carry out the method as follows.

[0072] In the melt polymerization process of the polyester resin according to the present invention, the polyester polymerization catalyst consisting of an aluminum compound and a phosphorus compound is used as a catalyst, and the melt polymerization conditions and the P / Al (molar ratio) in the polyester resin are set within a specific range, so that the process can be carried out by a method including conventionally known processes. For example, when producing PET, it is produced by a direct esterification method in which terephthalic acid and ethylene glycol, and if necessary, other copolymerization components are directly reacted, water is distilled off, esterification is performed, and then polymerization is performed under reduced pressure, or by a transesterification method in which dimethyl terephthalate and ethylene glycol, and if necessary, other copolymerization components are reacted, methyl alcohol is distilled off, transesterification is performed, and then polymerization is performed under reduced pressure. In order to promote crystallization before solid-phase polymerization, the melt-polymerized polyester resin may be absorbed and then heated and crystallized, or water vapor may be directly blown onto the polyester resin chips to cause heat crystallization. The melt polymerization reaction is preferably carried out in a continuous reactor. A continuous reactor is a method in which a reactor for esterification or transesterification and a melt polymerization reactor are connected by piping, and raw materials are continuously charged into each reactor without emptying, transferred to the melt polymerization reactor by piping, and the resin is withdrawn from the melt polymerization reactor. In this case, "continuous" does not necessarily mean that raw materials are charged and withdrawn at all times, but may be intermittent, in which raw materials are charged and withdrawn in small amounts, for example, about 1 / 10 of the volume of the reactor. In any of these methods, the esterification reaction or transesterification reaction may be carried out in one stage or in multiple stages, preferably in two to five stages, more preferably in three or four stages, and even more preferably in three stages.

[0073] In the present invention, the set value of the carboxyl terminal group concentration of the polyester oligomer supplied to the polymerization step is preferably 800 to 1500 eq / ton. More preferably, it is 800 to 1450 eq / ton. By setting the set value of the carboxyl terminal group concentration of the polyester oligomer within the above range, the activity of the polymerization catalyst can be fully utilized.

[0074] In the present invention, the ratio of the hydroxyl terminal group concentration to the total terminal group concentration of the polyester oligomer supplied to the polymerization step is preferably from 45 to 70 mol %, more preferably from 47 to 68 mol %.

[0075] The carboxyl end group concentration of the oligomer supplied to the polymerization step is preferably within the above-mentioned preferred range, and the fluctuation of the carboxyl end group concentration is preferably within ±6% of the set value. More preferably within ±5%, even more preferably within ±4%, and particularly preferably within ±3%. If the fluctuation of the carboxyl end group concentration exceeds ±6%, the uniformity of the quality of the obtained polyester resin may be reduced. On the other hand, the lower limit is most preferably ±0%, which means no fluctuation, but from the viewpoint of cost performance, ±0.2% is preferable, and ±0.5% is more preferable.

[0076] For example, when an esterification reaction is carried out using a plurality of esterification reaction tanks, in order to suppress the fluctuation in the carboxyl terminal group concentration of the polyester oligomer at the outlet of the final esterification reaction tank, which is the oligomer supplied to the polymerization step, it is important to suppress the fluctuation in the carboxyl terminal group concentration of the polyester oligomer at the outlet of the first esterification reaction tank, and by suppressing the fluctuation in this characteristic, the fluctuation in the carboxyl terminal group concentration of the polyester oligomer at the outlet of the final esterification reaction tank can be made extremely small. In addition, the fluctuation in the carboxyl terminal group concentration of the polyester oligomer at the outlet of the first esterification reaction tank is greatly influenced by the fluctuation in the heat quantity per unit time of the reactants retained in the first esterification reaction tank, so it is preferable to control the heat quantity fluctuation within an appropriate range.

[0077] That is, in a method for continuously producing a polyester resin by preparing a slurry consisting of a dicarboxylic acid and a glycol in a slurry preparation tank, continuously supplying the slurry to an esterification reaction tank, carrying out an esterification reaction using the esterification reaction tank, and then continuously supplying the slurry to a polymerization reaction tank for polymerization, it is preferable to suppress the carboxyl end group concentration at the outlet of the esterification reaction tank to which the slurry is supplied within a set value of ±10%. Within ±9% is preferable, within ±8% is more preferable, and within ±6% is even more preferable. By setting the range, it is possible to suppress the fluctuation of the carboxyl end group concentration of the oligomer at the outlet of the final esterification reaction tank within a preferable range, which leads to stabilization of the quality of the subsequent polymerization reaction and the obtained polyester resin, which is preferable. On the other hand, the lower limit is most preferably ±0%, which is no fluctuation, but from the viewpoint of cost performance, ±0.5% is preferable, and ±1.0% is more preferable. As a result, even if the control of the subsequent esterification reaction tank is at a conventionally known fluctuation level, the fluctuation of the carboxyl end group concentration of the polyester oligomer supplied to the polymerization step can be greatly suppressed.

[0078] Furthermore, in the above esterification reaction step, it is preferable to measure the carboxyl end group concentration and the hydroxyl end group concentration of the polyester oligomer online and feed back the results to the above-mentioned slurry temperature control system, thereby improving the control accuracy and stability.

[0079] The method for measuring the oligomer characteristics is not limited, but it is preferable to measure using a near-infrared spectrophotometer. It is preferable to continuously measure using a near-infrared spectrophotometer in a part where the oligomer flows, such as a reaction tank or piping. There is no particular limitation on the near-infrared spectrophotometer as long as it can perform continuous online measurement. For example, commercially available products such as near-infrared online analyzers manufactured by NIRS Systems (Nireco), BRAN+LUEBBE, and Yokogawa Electric Corporation may be used, or a systemized device may be manufactured for this purpose.

[0080] The detection cell of the near-infrared spectrophotometer must be installed in a high-temperature region, and must be designed to accommodate this. When the cell is installed between esterification reactors, the cell must be in a pressurized state, and when the cell is installed in a transfer line from the esterification reactor to the initial polymerization reactor, the cell must be designed to withstand both pressurization and depressurization. It is preferable to take appropriate measures depending on the installation location, etc.

[0081] The measurement cell of the near-infrared spectrophotometer may be installed at any location between the start of the esterification reaction and immediately before the start of the polymerization reaction. It may be installed in the esterification reaction tank or the transfer line of each reaction tank. It may be installed directly in each reaction tank or transfer line, or a bypass line may be provided and installed in the bypass line. When detecting the inside of a reaction tank when installed in the bypass line, it is preferable to install a circulation line in which the reaction contents are circulated in the target reaction tank and install the cell in the circulation line. Since the installed measurement cell may require maintenance, it is preferable to install the cell in the bypass line. In the present invention, since the carboxyl end group concentration of the oligomer at the outlet of the first esterification reaction tank is important as described above, it is preferable to install a bypass line in the transfer line from the first esterification reaction tank to the second esterification reaction tank and install a detector in the bypass line to measure the concentration. In addition, another detector may be installed in the transfer line from the final esterification reaction tank to the first polymerization reaction tank to measure the characteristic values ​​of both oligomers and improve the control accuracy. In the method of controlling the esterification reaction using a plurality of detectors, it is preferable to control the temperature of the slurry supplied to the first esterification reaction tank by feeding back the measured value measured by the detector installed in the transfer line at the outlet of the first esterification reaction tank. Control based on the measured value detected at another detection location may be fed back to a control system that changes another esterification reaction, for example, the amount of glycol for adjusting the esterification reaction supplied to the second esterification reaction tank. The control system that can most improve the accuracy may be appropriately selected and implemented.

[0082] The oligomer characteristics may be measured by measuring only the carboxyl end group concentration, or by simultaneously measuring both the carboxyl end group concentration and the hydroxyl end group concentration. When measuring at a plurality of locations, the measurement contents may be changed at each location. For example, it is preferable that the control system using a detector installed in the transfer line at the outlet of the first esterification reactor is controlled by the carboxyl end group concentration, and the control system using a detector installed in the transfer line at the outlet of the final esterification reactor is controlled by simultaneously measuring both the carboxyl end group concentration and the hydroxyl end group concentration so that both end group concentrations are within a predetermined range. The measurement wavelength of the near-infrared is not limited. It is preferable to use a model oligomer corresponding to the measurement location, and to investigate and appropriately set a wavelength that has high sensitivity and little disturbance. For example, it is preferable to use a wavelength of 1444 nm for the carboxyl end group concentration and a wavelength of 2030 nm for the hydroxyl end group concentration.

[0083] The calibration curves of the concentrations of both terminal groups quantified by the above method are preferably prepared using the above model oligomers. In this case, the carboxyl terminal group concentration and the hydroxyl terminal group concentration of the model oligomer are preferably values ​​measured by NMR.

[0084] In the present invention, the number and size of reaction vessels in the polymerization step and the production conditions for each step can be appropriately selected without any limitations.

[0085] For example, the polymerization reaction conditions in the case of a three-stage method of initial polymerization, middle polymerization, and final polymerization are as follows: the reaction temperature of the first polymerization stage is 250 to 290°C, preferably 260 to 280°C, the pressure is 2.6 to 65 kPa, preferably 4 to 27 kPa, and the temperature of the final polymerization stage is 265 to 300°C, preferably 265 to 290°C, and the pressure is 0.013 to 1.3 kPa, preferably 0.065 to 0.65 kPa. When carried out in three or more stages, the reaction conditions of the intermediate polymerization stage are between the reaction conditions of the first stage and the reaction conditions of the final stage. It is preferable that the degree of increase in the intrinsic viscosity reached in each of these polymerization reaction steps is smoothly distributed.

[0086] (Addition of polyester resin polymerization catalyst) In the present invention, the method and location of addition of the aluminum compound solution and the phosphorus compound solution are not limited. The aluminum compound solution and the phosphorus compound solution are preferably added simultaneously. The simultaneous addition includes a method of adding each separately to the same reaction tank or the piping between the reaction tanks, and a method of mixing the aluminum compound solution and the phosphorus compound solution in advance to form a single liquid and adding it. Examples of the method of forming a single liquid include a method of mixing each solution in a tank, and a method of merging the pipes for adding the catalyst in the middle and mixing them. When adding to the reaction tank, it is preferable to increase the stirring of the reaction tank. When adding to the pipes between the reaction tanks, it is preferable to install an in-line mixer or the like so that the added catalyst solution is quickly and uniformly mixed.

[0087] When the aluminum compound solution and the phosphorus compound solution are added separately, a large amount of foreign matter caused by the aluminum compound is likely to be generated, and the temperature-rise crystallization temperature may become low, the temperature-fall crystallization temperature may become high, and sufficient catalytic activity may not be obtained. By adding the aluminum compound and the phosphorus compound simultaneously, a complex of the aluminum compound and the phosphorus compound that brings about polymerization activity can be quickly and efficiently formed, but when they are added separately, the formation of the complex of the aluminum compound and the phosphorus compound is insufficient, and the aluminum compound that could not form a complex with the phosphorus compound may precipitate as a foreign matter. The aluminum compound solution and the phosphorus compound solution are preferably added after the esterification reaction or the ester exchange reaction is completed, since adding them before the esterification reaction or the ester exchange reaction may increase the amount of aluminum-based foreign matter.

[0088] (Polyester resin solid-state polymerization process) In the present invention, as a method for reducing the CT amount, it is preferable to perform additional polymerization of the polyester resin produced in the melt polymerization step in a solid-phase polymerization step. The solid-phase polymerization is carried out by converting the polyester obtained in the melt polymerization step into a powdered or granular form. The powdered or granular form means polyester in chip, pellet, flake, or powder form, and is preferably chip or pellet, and it is desirable that the average particle size is usually 2.0 to 5.5 mm, preferably 2.2 to 4.0 mm.

[0089] The solid-phase polymerization is carried out by heating the powdery polyester at a temperature below the melting point of the polyester under an inert gas flow or under reduced pressure. The solid-phase polymerization process consists of at least one stage, and the polymerization temperature is usually 190 to 235°C, preferably 195 to 230°C. In the case of the inert gas flow method, the pressure is usually 0.98 MPa to 0.0013 MPa, preferably 0.49 MPa to 0.013 MPa, and the process is carried out under an inert gas flow such as nitrogen, argon, or carbon dioxide, and in the case of the reduced pressure method, the pressure is usually 13 to 39000 Pa, preferably 13 to 13300 Pa. The higher the temperature, the shorter the time required for the solid-phase polymerization to reach the desired physical properties, and the solid-phase polymerization time is usually 1 to 50 hours, preferably 5 to 30 hours, and more preferably 10 to 25 hours.

[0090] The granular polyester to be supplied to the solid-phase polymerization step may be pre-crystallized by heating to a temperature lower than the temperature at which the solid-phase polymerization is carried out, and then supplied to the solid-phase polymerization step.

[0091] Such a preliminary crystallization step may be carried out by heating the granular polyester in a dry state at a temperature of usually 120 to 200°C, preferably 130 to 180°C, for 1 minute to 4 hours, or by heating the granular polyester in a water vapor atmosphere, a water vapor-containing inert gas atmosphere, or a water vapor-containing air atmosphere at a temperature of usually 120 to 200°C for 1 minute or more.

[0092] The polyester melt-polymerized as described above is, for example, chipped and then transported through a transport pipe to a storage silo or a solid-phase polymerization process. If such chips are transported by a forced low-density transport method using air, for example, a large impact force is applied to the surface of the melt-polymerized polyester chips by collision with the pipe, resulting in the generation of a large amount of fines and film-like substances. Such fines and film-like substances have the effect of promoting the crystallization of polyester, and if they are present in large amounts, the transparency of the obtained molded product becomes very poor. Therefore, adding a process of removing such fines and film-like substances is one of the preferred embodiments.

[0093] The method for removing the fines and film-like substances is not limited, and examples thereof include a method of treating the solids in a vibrating sieve process, an air current classification process, a gravity classification process, or the like, which are separately installed in an intermediate process between the solid-state polymerization process and a subsequent process installed after the solid-state polymerization process.

[0094] The polyester obtained by the production method of the present invention can be subjected to a contact treatment with water after solid-phase polymerization in order to further prevent mold contamination caused by adhesion of oligomers such as cyclic trimers to the inner surface of the mold, the gas exhaust port of the mold, exhaust pipe, etc. during molding. The method is not limited, but examples include a method of immersing in water and a method of pouring water on the chips with a shower. The treatment time is 5 minutes to 2 days, preferably 10 minutes to 1 day, and more preferably 30 minutes to 10 hours, and the water temperature is 20 to 180°C, preferably 40 to 150°C, and more preferably 50 to 120°C.

[0095] The solid phase polymerization and the above-mentioned accompanying treatments in the present invention may be carried out either batchwise or continuously, but a continuous process is preferred from the viewpoints of uniformity in the quality of the obtained polyester and economic efficiency.

[0096] In the present invention, the degree of polymerization of the polyester may be appropriately set in accordance with the required properties of the intended use of the polyester to be obtained. In general, however, it is preferable to obtain a polyester having an intrinsic viscosity of 0.3 to 0.65 dl / g by melt polymerization, and then increase the intrinsic viscosity of the polyester obtained by the melt polymerization to 0.60 to 1.20 dl / g by solid-phase polymerization.

[0097] (Method of manufacturing a blow molded polyester resin product) The method for producing the polyester resin blow molded article of the present invention is not limited, but is preferably carried out by the following method.

[0098] In the blow molding of heat-resistant bottles, a precursor with a bottom, generally called a preform, is created, which is blown and stretched in a mold and then heat-set. Methods such as compression molding and injection molding are used to manufacture preforms. For example, in injection molding, a preform can be obtained by heating and melting the material to 260-300°C and injecting it into a preform mold. Usually, a preform has a thick test tube shape with a gate at the bottom and a cap screw engraved on the mouth.

[0099] In the case of a heat-resistant bottle, the mouth of the preform obtained is crystallized. By crystallizing, it is possible to prevent the mouth from being deformed even when a high-temperature content is filled. The crystallization of the mouth is preferably performed by heating to 130 to 200°C, more preferably 140 to 190°C. As a heating method, an infrared heater, hot air, induction heating, immersion in an oil bath, etc. can be used, and the use of an infrared heater is preferable from the viewpoint of productivity. The heat crystallization of the mouth may be performed after blow molding.

[0100] The preform is heated, stretched in the length direction (vertical direction) of the bottle, and blow molded in the circumferential direction to obtain a bottle. Stretching is usually performed in the length direction with a bar-shaped stretching rod, and pressurized gas such as air or nitrogen is used in the circumferential direction. The pressurized gas is preferably 1 to 10 MPa. A method in which pressurized gas is blown while inserting a stretching rod to simultaneously stretch in the length direction and the circumferential direction is preferable, but stretching in the length direction and then in the circumferential direction may be performed. Heating is performed using an infrared heater, hot air, induction heating, etc. The heating temperature is usually 80 to 130°C, and preferably 90 to 120°C.

[0101] The lower limit of the stretch ratio in the bottle length direction is preferably 1.5 times, more preferably 2 times. If it is less than the above, stretching may become uneven. The upper limit of the stretch ratio in the length direction is preferably 6 times, more preferably 5 times, and even more preferably 4 times. If it exceeds the above, breakage or the like is likely to occur.

[0102] The lower limit of the stretch ratio in the circumferential direction of the bottle is preferably 2 times, more preferably 2.5 times. If it is less than the above, stretching may become uneven. The upper limit of the stretch ratio in the circumferential direction is preferably 6 times, more preferably 5 times, and even more preferably 4 times. If it exceeds the above, breakage or the like is likely to occur.

[0103] When heat setting is performed in the same mold subsequent to blow molding, the lower limit of the mold temperature for blow molding is preferably 80° C., more preferably 120° C., even more preferably 130° C., and most preferably 140° C. If the temperature is lower than the above range, crystallization may not be sufficiently promoted in the subsequent heat setting, resulting in insufficient heat resistance, or a longer heat setting time may be required, resulting in reduced productivity.

[0104] The upper limit of the mold temperature is preferably 200° C., more preferably 190° C., further preferably 180° C., and particularly preferably 170° C. If the mold temperature is high, mold contamination increases, and the number of times continuous molding is possible may decrease.

[0105] The blow-molded bottle is subsequently heat-set in the mold. The lower limit of the heat-set time is preferably 0.5 seconds, more preferably 1 second, and even more preferably 1.5 seconds. If the heat-set time is less than the above, crystallization is not sufficiently promoted, and heat resistance may be insufficient. The upper limit of the heat-set time is 15 seconds, preferably 10 seconds, and more preferably 5 seconds. A long heat-set time not only reduces productivity, but also requires a large number of molds in the case of a rotary blow molding machine, which may result in poor economic efficiency if the device becomes large. After heat-setting in the mold, additional heat-setting may be performed by heating with infrared rays, hot air, induction heating, etc.

[0106] It is also possible to carry out the blow molding in a mold at 5 to 50° C., followed by heat setting in a heated mold. In this case, the temperature of the heat setting mold is the same as the mold temperature in the above case.

[0107] The blow molding device may be equipped with one mold, but for mass production, it is preferable to have multiple molds that move in sequence between a location where the heated preform is set in the mold, a location where it is stretched, a location where it is heat set, and a location where the bottle is ejected.

[0108] Although the cold parison method in which a cooled preform is reheated has been described above, a hot parison method in which blow molding is performed without completely cooling the preform is also possible.

[0109] The capacity of the bottle to be molded is preferably 200 mL to 6 L. Particularly, it is preferably 300 mL to 2 L. The shape of the bottle body can be any shape, such as a circle, a square (including a shape with the corners cut off), or a hexagon.

[0110] This application claims the benefit of priority based on Japanese Patent Application No. 2020-056876, filed on March 26, 2020. The entire contents of the specification of Japanese Patent Application No. 2020-056876, filed on March 26, 2020, are incorporated by reference into this application. EXAMPLES

[0111] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. The evaluation methods used in each example and comparative example are as follows.

[0112] [Evaluation method] (1) Intrinsic viscosity (IV) of polyester resin The polyester resin was dissolved in a 6 / 4 (weight ratio) mixed solvent of phenol / 1,1,2,2-tetrachloroethane, and the measurement was performed at 30°C.

[0113] (2) Quantitative determination of the total amount of phosphorus present in the polyester resin bound to the hydroxyl end groups of the polyester relative to the total amount of phosphorus present in the polyester resin (2-1)P-NMR spectrum measurement 420 mg of polyester resin was dissolved in 2.7 mL of a mixed solvent of hexafluoroisopropanol + deuterated benzene (1+1), and 10 μL of a 25% phosphoric acid solution in deuterated acetone was added and centrifuged. Then, 100 to 150 mg of trifluoroacetic acid was added to the supernatant, and P-NMR measurement was immediately performed. Note that the method for measuring the amount of phosphorus compounds bound to polyester end groups is not limited to the above method, and any method can be used as long as it can confirm the peaks corresponding to the above (chemical formula 1) to (chemical formula 3) (hereinafter referred to as "three types of phosphorus compounds bound to polyester end groups"). Equipment: Fourier transform nuclear magnetic resonance equipment (BRUKER, AVANCE500) 31P resonance frequency: 202.456MHz Lock solvent: deuterated benzene Detection pulse flip angle: 65° Data capture time: 1.5 seconds Delay time: 0.5 seconds Proton decoupling: Full decoupling Measurement temperature: 25~35℃ Number of times: 20,000 to 30,000 times

[0114] (2-2) Quantification method In the spectrum obtained in (2-1) above, six peaks were observed at 27-38 ppm and 0-3 peaks at 50-55 ppm. The three peaks corresponding to the three types of phosphorus compounds bonded to polyester end groups are three peaks that have almost no shift change compared to the other three peaks that do not correspond to the three types of phosphorus compounds bonded to polyester end groups, even when the amount of trifluoroacetic acid is changed by about 10-20% within the above-mentioned range of addition, among the peaks appearing at 27-38 ppm, and the chemical shift values ​​were 28.8±0.3 ppm for the first peak, 30.1±0.3 ppm for the second peak, and 30.5±0.3 ppm for the third peak. The shift difference between the first peak and the second peak was 1.3±0.1 ppm, and the shift difference between the second peak and the third peak was 0.4±0.1 ppm. The ratio of the integral values ​​of these three peaks to the total integral values ​​of the peaks corresponding to all phosphorus compounds was calculated and shown as a, b, and c in Table 4. The total value of the above a to c was defined as the amount of phosphorus compounds bound to the polyester terminals (the total amount of phosphorus elements contained in the three types of phosphorus compounds bound to the polyester terminal groups relative to the total amount of phosphorus elements present in the polyester resin).

[0115] (3) Determination of aluminum element in polyester resin (dry decomposition method) Polyester resin was weighed into a platinum crucible, carbonized on an electric stove, and then incinerated in a muffle furnace at 550°C for 8 hours. The incinerated sample was treated with 6M hydrochloric acid, and then diluted with 1.2M hydrochloric acid to a constant volume of 20mL. Metal concentrations were determined by ICP emission measurement. Equipment: SPECTRO CIROS-120 Plasma power: 1400W Plasma gas: 13.0L / min Auxiliary gas: 2.0L / min Nebulizer: Crossflow nebulizer Chamber: Cyclone chamber Measurement wavelength: 167.078nm

[0116] (4) Determination of phosphorus in polyester resin (molybdenum blue colorimetric method) The polyester resin was decomposed in a wet process using sulfuric acid, nitric acid, and perchloric acid, and then neutralized with aqueous ammonia. Ammonium molybdate and hydrazine sulfate were added to the prepared solution, and the absorbance at a wavelength of 830 nm was measured using a UV-Visible spectrophotometer (Shimadzu Corporation, UV-1700).

[0117] (5) Amount of aluminum-based foreign matter 30 g of polyester resin and 250 mL of a mixed solution of parachlorophenol / tetrachloroethane (3 / 1: weight ratio) were placed in a 500 mL Erlenmeyer flask containing a stirrer, and dissolved by heating at 100 to 105°C for 1.5 hours using a hot stirrer. The solution was filtered to remove foreign matter using a polytetrafluoroethylene membrane filter (PTFE membrane filter manufactured by Advantec, product name: T100A047A) with a diameter of 47 mm and a pore size of 1.0 μm. The effective filtration diameter was 37.5 mm. After filtration, the filter was washed with 50 mL of chloroform and then dried. The amount of aluminum element on the filtration surface of the membrane filter was quantified using a scanning type X-ray fluorescence analyzer (RIGAKU, ZSX100e, Rh line bulb 4.0 kW). Quantification was performed on the central part of the membrane filter with a diameter of 30 mm. The calibration curve for the X-ray fluorescence analysis was obtained using polyethylene terephthalate resin with a known aluminum element content, and the apparent amount of aluminum element was expressed in ppm. The measurement was performed by measuring the Al-Kα line intensity under the conditions of PHA (pulse height analyzer) 100-300, using pentaerythritol as a spectroscopic crystal and a PC (proportional counter) as a detector, with an X-ray output of 50 kV-70 mA. The amount of aluminum element in the PET resin for the calibration curve was quantified using high-frequency inductively coupled plasma emission spectrometry.

[0118] (6) Quantification of CT and ΔCT Solid-phase polymerized polyester resin or polyester resin blow molded body molded by the method described below was frozen and crushed or fragmented, and 100 mg of sample was precisely weighed out. This was dissolved in 3 mL of a hexafluoroisopropanol / chloroform mixture (volume ratio = 2 / 3) and further diluted with 20 mL of chloroform. 10 mL of methanol was added to this to precipitate the polymer, and then filtered. The filtrate was evaporated to dryness and made to a constant volume with 10 mL of dimethylformamide. The amount of cyclic trimer was then quantified by the following high performance liquid chromatography method. The CT amount indicates the amount of cyclic trimer in the solid-state polymerized polyester resin. The ΔCT amount is the amount of cyclic trimer in the polyester resin blow molded product minus the amount of cyclic trimer in the solid-state polymerized polyester resin. The total CT amount (= CT amount + ΔCT amount) is the amount of cyclic trimer in the polyester resin blow molded product. Equipment: L-7000 (Hitachi) Column: μ-Bondasphere C18 5μ 100 angstroms 3.9 mm × 15 cm (Waters) Solvents: Eluent A: 2% acetic acid / water (v / v) Eluent B: Acetonitrile Gradient B%: 10→100% (0→55 min) Flow rate: 0.8ml / min Temperature: 30℃ Detector: UV-259nm

[0119] (7) Preparation of aluminum compounds A 20 g / L aqueous solution of basic aluminum acetate and an equal amount (volume ratio) of ethylene glycol were charged into a blending tank and stirred at room temperature for several hours. After that, the water was distilled off from the system while stirring at 50-90°C under reduced pressure (3 kPa) for several hours, preparing an ethylene glycol solution containing 20 g / L of an aluminum compound.

[0120] (8) Preparation of phosphorus compounds Irganox1222 (manufactured by BASF) was charged as a phosphorus compound together with ethylene glycol in a mixing tank, and heated at a liquid temperature of 175°C for 2.5 hours while stirring under nitrogen substitution to prepare an ethylene glycol solution containing 50g / L of phosphorus compound. The molar fraction of the phosphorus compound represented by (chemical formula 4) in the obtained solution was 40%, and the molar fraction of the compound structurally changed from (chemical formula 4) was 60%.

[0121] Examples 1 and 2, Comparative Examples 1 and 2 (Melt polymerization process) A continuous polyester production apparatus consisting of three continuous esterification reaction tanks and three polycondensation reaction tanks, and an in-line mixer having a high-speed agitator is installed on the transfer line from the third esterification reaction tank to the first polycondensation reaction tank, was continuously fed with a slurry prepared by mixing 0.75 parts by mass of ethylene glycol with 1 part by mass of high-purity terephthalic acid, and reacted according to the temperature, pressure and residence time listed in Table 3 to obtain a low-order condensate. The low-order condensate was continuously transferred to a continuous polycondensation apparatus consisting of three reaction tanks, and polycondensed according to the temperature, pressure and residence time listed in Table 3 to obtain a polyester resin (PET) with an IV of 0.554 dl / g. The polyester resin was extruded into a strand shape, cooled in water, and then cut into chips with an average particle weight of 23.5 mg. In order to eliminate the influence of the previous batch and ensure a high-quality product, the polyester resin was collected after 30 hours or more had elapsed since the start of operation or after the conditions were changed. The ethylene glycol solution containing 20 g / L of the aluminum compound prepared by the above method and the ethylene glycol solution containing 50 g / L of the phosphorus compound prepared by the above method were added from the in-line mixer so that the remaining amounts after completion of polymerization were the amounts shown in Table 4 relative to the mass of the obtained polyester resin.

[0122] [Table 3]

[0123] (Solid phase polymerization process) The resulting chips were then transported to a continuous solid-state polymerization apparatus. They were crystallized at about 155°C under a nitrogen atmosphere, and then preheated to about 200°C under a nitrogen atmosphere, and sent to a continuous solid-state polymerization reactor for solid-state polymerization at about 207°C under a nitrogen atmosphere. The chips were then subjected to a vibrating sieve separation process and an air classification process to remove fines and film-like materials, yielding a polyester resin with an IV of 0.735 dl / g.

[0124] (Method of manufacturing a blow molded polyester resin product) The polyester resin was dried in a vacuum dryer to reduce the moisture content to 100 ppm or less, and a bottomed preform was molded using a Meiki M-150C-DM injection molding machine and a preform mold (mold temperature 5°C). The plasticization conditions for the M-150C-DM injection molding machine were feed screw rotation speed 70%, screw rotation speed 120 rpm, back pressure 0.5 MPa, and cylinder temperatures were set to 45°C, 250°C, and 290°C after the nozzle, in that order, from directly below the hopper. The injection pressure and dwell pressure were also adjusted so that the molded product weight was 28.4 ± 0.2 g. Next, the mouth of the preform was heat crystallized using an NC-01 mouth crystallizer manufactured by Frontier Co., Ltd. Furthermore, using an SBO Lab N°1045 Type 1 Lab blow molding machine manufactured by Sidell Co., Ltd., the preform was biaxially stretch-blow-molded at a magnification of 2.5 times in the longitudinal direction and 3.8 times in the circumferential direction in a molding cycle of 30 seconds at 750 bph while blowing air at a pressure of 36 bar into a mold set at 160°C.

[0125] Table 4 shows the conditions of the final melt polymerization tank (third polymerization tank) for the polyester resins obtained in Examples 1 and 2 and Comparative Examples 1 and 2, and the property values ​​of the blow molded articles made of the polyester resins.

[0126] [Table 4]

[0127] In Table 4, the CT amount is the measured value of the cyclic trimer contained in the solid-phase polymerization product of the polyester resin, and the total CT amount (=CT amount + ΔCT amount) is the measured value of the cyclic trimer contained in the blow molded body made of polyester resin. The amount of aluminum-based foreign matter and the amount of end-blocked phosphorus compounds are the measured values ​​of the polyester resin obtained by the melt polymerization process. Since the amount of aluminum-based foreign matter and the amount of end-blocked phosphorus compounds hardly change during the solid-phase polymerization treatment and blow molding evaluation, the amounts of solid-phase polymerization product of polyester resin and blow molded body made of polyester resin were considered to be approximately the same as the measured values ​​in Table 4. The reason why the amount of aluminum-based foreign matter and the amount of end-blocked phosphorus compounds do not change during the solid-phase polymerization and blow molding processes is believed to be due to the low temperature in the solid-phase polymerization process and the extremely short residence time in the blow molding process.

[0128] The polyester resin and polyester resin blow molded article of Examples 1 and 2 have small CT amounts and total CT amounts (CT amount + ΔCT amount), and are of higher quality than the polyester resin and polyester resin blow molded article of Comparative Examples 1 and 2.

[0129] Using the results of the examples and comparative examples in Table 4, the relationship between T×RT×(P / Al) and CT and ΔCT is shown in Figure 1, the relationship between T×RT×(P / Al) and the total CT amount (CT amount + ΔCT amount) is shown in Figure 2, the relationship between T×RT×(P / Al) and the amount of end-capped phosphorus compound is shown in Figure 3, the relationship between the amount of end-capped phosphorus compound and the total CT amount (CT amount + ΔCT amount) is shown in Figure 4, and the relationship between the amount of end-capped phosphorus compound and the solid-state polymerization rate is shown in Figure 5.

[0130] From these figures, it is clear that the scope of the present invention is critical, and that the CT amount and the ΔCT amount are a trade-off phenomenon. [Industrial Applicability]

[0131] The present invention relates to a method for producing a polyester resin, and uses a polymerization catalyst consisting of an aluminum compound and a phosphorus compound, in which a metal component other than antimony, germanium, and titanium is the main metal component of the catalyst. The polyester resin obtained using the polymerization catalyst has various stabilities such as color tone and heat resistance, which are characteristic of the polyester resin, and is highly transparent because the generation of aluminum-based foreign matter is suppressed. In addition, since a part of the hydroxyl group terminal of the polyester resin is blocked by a phosphorus compound, the generation of CT and ΔCT in the polyester resin production process and the molding process in which the polyester resin is blow molded is suppressed, and the effect of suppressing mold contamination for molding is expressed, and further, the solid-phase polymerization rate can be improved. Therefore, it is a great contribution to the industrial world.

Claims

1. A method for producing a polyester resin containing 85 mol % or more of ethylene terephthalate structural units, comprising the steps of: a melt polymerization step in which an aluminum compound and a phosphorus compound are used as polymerization catalysts to continuously melt-polymerize in two or more polymerization tanks, and the polymerization in the final polymerization tank satisfies the condition of the following formula (I); A method for producing a polyester resin, comprising the steps of: performing solid-phase polymerization after the melt polymerization step; 410≦T×RT×(P / Al)≦580… (I) [In the above formula (I), T represents the temperature (° C.) of the final polymerization tank, RT represents the residence time (hours) in the final polymerization tank, and P / Al represents the molar ratio of phosphorus element to aluminum element in the polyester resin.]

2. 2. The method for producing a polyester resin according to claim 1, wherein the phosphorus compound is heat-treated in a solvent at 150 to 200° C.

3. 3. The method for producing a polyester resin according to claim 1, wherein the phosphorus compound is at least one selected from the group consisting of phosphonic acid compounds and phosphinic acid compounds.

4. 4. The method for producing a polyester resin according to claim 1, wherein the total amount of phosphorus elements bonded to hydroxyl terminals of the polyester is 42 to 60 mol % based on the total amount of phosphorus elements present in the polyester resin.

5. 5. The method for producing a polyester resin according to claim 1, wherein the amount of cyclic trimer in the polyester resin is 3,300 ppm or less.

6. The method for producing a polyester resin according to any one of claims 1 to 5, wherein the moisture content of the polyester resin is set to 100 ppm or less, and the amount of cyclic trimer generated when melt-molded at a cylinder temperature of an injection molding machine of 290°C is 650 ppm or less.

7. The method for producing a polyester resin according to any one of claims 1 to 6, wherein the structure of the phosphorus compound bonded to the hydroxyl group terminal of the polyester resin is at least one of the following (Chemical Formula 1) to (Chemical Formula 3). 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】

8. The method for producing a polyester resin according to any one of claims 1 to 7, wherein the content of aluminum element in the polyester resin is 13 to 25 ppm.

9. 9. The method for producing a polyester resin according to claim 1, wherein a molar ratio of phosphorus element to aluminum element (P / Al) in the polyester resin is 1.5 to 3.

5.

10. A method for producing a polyester resin blow molded article, comprising a step of blow molding a polyester resin produced by the method for producing a polyester resin according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Washing machine utilizing knocking motion

    JP1977099655A

  • Production of polyester of high degree of polymerization

    JP1986255928A

  • Polyester resin and hollow container

    JP1998110026A

  • Polyester polymerization catalyst, polyester prepared using the same and polyester preparing method

    JP2004256633A

  • Process for producing polyester

    JP2007211045A